Clinical and Genetic Risk Factors of Recurrent Nonalcoholic Fatty Liver Disease After Liver Transplantation. Issue 2 (5th February 2021) - Satapathy, Sanjaya K.; Tran, Quynh T.; Kovalic, Alexander J.; Bontha, Sai Vineela; Jiang, Yu; Kedia, Satish; Karri, Saradashri; Mupparaju, Vamsee; Podila, Pradeep S. B.; Verma, Rajanshu; Maluf, Daniel; Mas, Valeria; et al.
Abstract : INTRODUCTION: Nonalcoholic fatty liver disease (NAFLD) has been increasingly reported among recipients of liver transplantation (LT). We aimed to identify clinical and genetic risk factors responsible for the development of early recurrent NAFLD in nonalcoholic steatohepatitis transplant recipients. METHODS: Forty-six total single nucleotide polymorphisms with known association with NAFLD were tested among both recipient and donor liver samples in 66 LT recipients with nonalcoholic steatohepatitis to characterize influences on NAFLD recurrence at ∼1 year post-LT (median interval from LT to biopsy: 377 days). RESULTS: Recurrent NAFLD was identified in 43 (65.2%) patients, 20 (30.3%) with mild recurrence, and 23 (34.8%) with moderate to severe NAFLD. On adjusted analysis, change in the body mass index (BMI) (ΔBMI) was significantly associated with NAFLD recurrence, whereas post-LT diabetes mellitus was associated with increased severity of NAFLD recurrence. ADIPOR1 rs10920533 in the recipient was associated with increased risk of moderate to severe NAFLD recurrence, whereas the minor allele of SOD2 rs4880 in the recipient was associated with reduced risk. Similar reduced risk was noted in the presence of donor SOD2 rs4880 and HSD17B13 rs6834314 polymorphism. DISCUSSION: Increased BMI post-LT is strongly associated with NAFLD recurrence, whereas post-LT diabetes mellitus was associated with increased severity of NAFLD recurrence. Both donor and recipient SOD2 rs4880 and donor HSD17B13 rs6834314 single nucleotide polymorphisms may be associated with reduced risk of early NAFLD recurrence, whereas presence of the minor allele form of ADIPOR1 rs10920533 in the recipient is associated with increased severity NAFLD recurrence.